A kidney-targeted MOF nanozyme combats calcium oxalate crystal-induced kidney injury - Xuhong He; Min Zhou; Zhengxin Liang; Shiyi Jin; Kunze Yu; Longxiyu Meng; Zhicong Tan; Jinming Xu; Jiaju Xu; Chongjun Xiang; Jingchao Wei; Wenjun Gao; et al. (Chemical Engineering Journal, 2026)

A study on the multiscale mass transfer and desorption mechanisms of CO₂ capture using composite amine solutions under low-concentration flue gas conditions - Yuhan Guo; Zebiao Jiang; Yu Zheng; Bohan Xiao; Yunxia Zhao (Journal of Environmental Chemical Engineering, 2026)

Ultrasound-induced modifications in egg-milk yogurt: a comprehensive study on physicochemical stability, lipidomic restructuring, and flavor profile enhancement - Danrong Yu; Yaogui Sun; Ni Zhang; Yutong Han; Bohan Wang; Shurong Wang; Ling Ma; Zhihui Yu (Food Chemistry, 2026)

A hybrid framework for quantitative source apportionment and ecological-health hazard of PAHs pollution around an abandoned coking plant - Houwei Ji; Bohan Jia; Qingchun Yang; Yu Bai; Han Gui; Fujun Ma; Jordi Delgado Martín (Process Safety and Environmental Protection, 2026)

Multi-objective optimization of ship resistance and seakeeping using an improved Voronoi-based parallel sequential sampling method - Dongqin Li; Yu Zhang; Yanqing Yin; Wenwen Chen; Bohan Wang; Zishuai Wang; Lingfeng Lu (Ocean Engineering, 2026)

Auxin signaling networks and hormonal cross-talk in plant responses to biotic stress - Yu Bai; Bohan Yang; Chang Wang; Yu Zhang; Isack Ibrahim Mrisho; Fasih Ullah Haider; Liquan Guo; Elshan Musazade (Planta, 2026)

Regulatory mechanism of feed conversion efficiency in largemouth bass (Micropterus salmoides): Insights from an integrated analysis of whole-genome resequencing, transcriptomics, and metabolomics - Bohan Zhang; Shijie Yuan; Daoyang Yu; Wenge Ma; Xiao Ma; Limin Wu; Xue Tian; Khor Waiho; Hanafiah Fazhan; Ruwei Xu; Xuejun Li; Xi Shi (Marine Life Science & Technology, 2026)

Metabolic basis of quality deterioration in soybean variety Heihe 43 driven by storage time: Based on non-targeted metabolomics - Xue Chen; Bohan An; Junjie Gao; Xintong Jiang; Bin Liu; Hansong Yu; Hongling Fu; Bo Lyu; Wendan Jing; Sainan Wang (Food Research International, 2026)

Plasma-activated nanocellulose for sustainable Pickering emulsions: Enhanced stability and antibacterial performance - Zhuo Li; Rusen Zhou; Bohan Chen; Baolin Yu; Mengying Zhu; Xiaoran Wang; Jiangling Shu; Dehui Xu; Lu Liu; Yadong Zhao; Renwu Zhou; Dingxin Liu (Carbohydrate Polymers, 2026)

Viral subversion of neddylation: dual roles in replication efficiency and evasion of antiviral immunity - Xiaoli Mo; Bohan Yu; Xudong Tang (Archives of Virology, 2026)

Numerical Simulation Analysis of Hydrodynamic Coupling Effects and Energy Conversion Efficiency of Dual-Float Wave Energy Converters - Dongqin Li; Yu Zhang; Jie Hu; Yanqing Yin; Bohan Wang; Wenwen Chen (Journal of Marine Science and Engineering, 2026)
This study examines the hydrodynamic performance and energy conversion mechanisms of a dual-float wave energy converter (WEC) to address the limitations of single-float WECs regarding energy capture efficiency and cost-effectiveness. A three-dimensional numerical wave tank is constructed utilizing computational fluid dynamics (CFDs) technology and STAR-CCM+ to simulate the dynamic response of the dual-float system under specific wave conditions characterized by a height of 0.1 m and a period of 1.5 s. The effects of a front-rear configuration with a quarter-wavelength spacing on the converter’s power output, turbofan rotational characteristics, and heave motion are systematically analyzed. The results indicate that the wave-facing float attains a consistent rotational speed of 4 rad/s, exhibiting significant fluctuations in heave displacement and velocity. Conversely, the downstream float exhibits diminished motion amplitude, a constant rotational velocity of 2.5 rad/s, and curtailed power generation attributable to wave diffraction and energy shielding from the wave-facing float. The mutual hydrodynamic interference between the floats influences the total energy conversion efficiency, as evidenced by the dual-float system’s array impact factor of 0.989. A parametric study covering multiple wave conditions and float spacing is supplemented to reveal the influence law of key parameters on system performance. This paper elucidates the fundamental mechanism of hydrodynamic coupling in dual-float arrays and offers a theoretical foundation and technical guidance for the optimal design and engineering application of arrayed WECs.

Transfer matrix modeling of tunnel with flexible joints subjected to strike-slip fault movements - Linkun Huang; Lianjin Tao; Xu Zhao; Yu Zhang; Bohan Song; Shuya Li (Soil Dynamics and Earthquake Engineering, 2026)

Cold adaptation mechanisms in Heterococcus viridis: Insights from morphological, physiological, and transcriptomic analyses - Qian Deng; Yongxin Zhang; Ziqing Liu; Bohan Yu; Chengwu Zhang; Miao Cui; Baoyan Gao (Algal Research, 2026)

Dibenzofuran-based blue hot exciton materials as hosts: Enabling high-efficiency and long-lifetime solution-processed OLEDs - Lveting Zhang; Mingke Li; Shipan Wang; Pengfei Niu; Wenle Tan; Bohan Wang; Yichao Chen; Feng Peng; Lei Ying; Yue Yu; Yuguang Ma (Chemical Engineering Journal, 2026)

Co-hydrothermal carbonization of the main components in food wastes: products characteristics and synergistic effects - Xiao Wei; Zenghui Ma; Shiguang Jin; Tengfei Wang; Xueqin Li; Yinxue Li; Yongkang Wang; Bohan Zhang; Yanling Yu (Journal of Environmental Management, 2026)

Interfacial damage mechanisms in hot-recycled asphalt mixtures: A molecular dynamics study considering the blending level between virgin and aged asphalt - Chengwei Xing; Mingchen Li; Ruihan Yu; Tian Jin; Bohan Zhu (Fuel, 2026)

Raw materials, preparation methods and applications of nanogels - Junjie Gao; Bohan An; Hao Gong; Hongling Fu; Hansong Yu (Food Research International, 2025)

Integrative single-cell and bulk RNA-seq analysis identifies glycosyltransferases-related signature in triple negative breast cancer - Junyi Hu; Ningning Yuan; Zhenglan Huang; Yancheng Liu; Bohan Tu; Xinyue Yu; Tianli Hui; Guowei Zuo (Functional & Integrative Genomics, 2025)

Improved chemical and gastrointestinal stability of natural proanthocyanidins encapsulated in hydrolyzed soy protein-based nanoparticles - Hongling Fu; Hao Gong; Junjie Gao; Bohan An; Xue Chen; Bin Liu; Bo Lyu; Wendan Jing; Hansong Yu (Food Research International, 2025)

The pivotal role of hydroxylamine in the anammox-based processes: Mechanisms and practical applications - Junhao You; Bohan Yu; Jianyong Liu (Chemical Engineering Journal, 2025)

Intelligent FA/FNA alternating strategy for nitrite-oxidizing bacteria inhibition: Data-driven prediction and process control - Chenlong Bu; Siyuan Wang; Bohan Yu; Fabien Pfaender; Tianxing Zhu; Yu-You Li; Jianyong Liu (Journal of Environmental Management, 2025)

Porphyromonas gingivalis induced DNA oxidative stress damage by iron overload to deplete CTCF expression and prevent osteogenic differentiation of periodontal ligament stem cells - Ying Zhang; Chenchen Si; Changyi Yang; Aijuan Wang; Bohan Yu (Journal of Molecular Histology, 2025)

Construction and immunogenicity analysis of a recombinant baculovirus targeting the N protein of SARS-CoV-2 - Bohan Yu; Xiaoli Mo; Li Sui; Yujia Fang; Xudong Tang; Ping Qian (Biotechnology Letters, 2025)

A large-scale integrated transcriptomic atlas for soybean organ development - Jingwei Fan; Yanting Shen; Chuan Chen; Xi Chen; Xiaoyue Yang; Haixia Liu; Ruiying Chen; Shulin Liu; Bohan Zhang; Min Zhang; Guoan Zhou; Yu Wang; et al. (Molecular Plant, 2025)

Effects of fuel elemental composition and combustion temperature on PM10 formation behaviors from combustion of municipal solid waste and refuse-derived fuel - Tianyu Liu; Chang Wen; Dapeng Wang; Bohan Zhang; Fangqi Liu; Xin Yu; Dunxi Yu (Fuel, 2025)

Assessing vegetation dynamics and human impacts in natural and urban areas of China: Insights from remote sensing data - Yuan Zou; Wei Chen; Siliang Li; Tiejun Wang; Le Yu; Xiao Zhang; Min Xu; Bohan Jiang; Chunying Wu; Ramesh P. Singh; Alfredo Huete; Cong-Qiang Liu (Journal of Environmental Management, 2025)

Evaluation of the growth, lipid, and hydrocarbon accumulation abilities in five strains of Botryococcus braunii (races A, B, and L) (Trebouxiophyceae, Chlorophyta) - Bohan Yu; Pengyan Gong; Hu Zhang; Baoyan Gao; Chengwu Zhang (Algal Research, 2025)

Cyclic response of unsaturated weathered red mudstone: Experimental investigation and a cyclic model - Haiying Fu; Yuwei Zhong; Qionglin Li; Bohan Wu; Ran Yuan; Jing Ye; Haihong Yu (Soil Dynamics and Earthquake Engineering, 2024)

Steering CO2 electroreduction toward C2+ products by defect-engineered coordination microenvironments of Cu-MOFs - Bohan A; Xixiong Jin; Min Wang; Yang Wang; Weiren Chen; Zixuan Wei; Zongyuan Du; Ximeng Liu; Yu Wang; Lingxia Zhang (Chemical Engineering Journal, 2024)

Assigning strategic COD flow to enhance denitrification coupled with anaerobic digestion and anammox for systematic upgradation of advanced nitrogen removal from food waste digestate - Jie Tan; Min Ye; Chihao Lin; Bohan Yu; Yu-You Li; Jianyong Liu (Chemical Engineering Journal, 2024)

Advanced anaerobic digestion of household food waste pretreated by in situ-produced mixed enzymes via solid-state fermentation: Feasibility and application perspectives - Lianpei Zou; Zhuoying Qi; Hui Cheng; Bohan Yu; Yu-You Li; Jianyong Liu (Environmental Research, 2024)

Red light trade-off regulating the negative effects of nitrogen concentration to improve lipid and astaxanthin production in the filamentous green microalga Oedocladium carolinianum - Hu Zhang; Yingnan Tan; Ruihong Zhu; Jian Hong; Bohan Yu; Baoyan Gao; Chengwu Zhang (Algal Research, 2024)

A review on superiority of mycelial pellets as bio-carriers: Structure, surface properties, and bioavailability - Si Zhang; Yu Wang; Bohan Wang; Shenyan Wang (Journal of Water Process Engineering, 2024)

Microbial co-culture mediated by intercellular nanotubes during DMAC degradation: Microbial interaction, communication mode, and degradation mechanism - Jiachao Yao; Yu Mei; Bohan Yuan; Fengzhen Zheng; Zeyu Wang; Jun Chen (Environmental Research, 2024)

Formulation improvement of a concentrated enzyme detergent for high-speed rail trains through life cycle assessment methodology - Changyan Yang; Yu Gong; Yinhang Qu; Jiayi Li; Bohan Yang; Rui Li; Dorothy S. Zhang; Baowei Wang; Yigang Ding; Bo Zhang (Environment, Development and Sustainability, 2023)

Effects of Immune Cells on Intestinal Stem Cells: Prospects for Therapeutic Targets - Liyun Ma; Jianghong Yu; Huilu Zhang; Bing Zhao; Jun Zhang; Dongqin Yang; Feifei Luo; Bangting Wang; Bohan Jin; Jie Liu (Stem Cell Reviews and Reports, 2022)

Spatial-temporal pattern evolution and driving force analysis of ecological environment vulnerability in Panzhihua City - Xiaoai Dai; Yu Gao; Xuwei He; Ting Liu; Bohan Jiang; Huaiyong Shao; Yuanzhi Yao (Environmental Science and Pollution Research, 2021)

Impact of cropland displacement on the potential crop production in China: a multi-scale analysis - Bohan Yang; Xinli Ke; Jasper van Vliet; Qiangyi Yu; Ting Zhou; Peter H. Verburg (Regional Environmental Change, 2020)

NbGIS regulates glandular trichome initiation through GA signaling in tobacco - Yihua Liu; Dongdong Liu; Ali Raza Khan; Bohan Liu; Minjie Wu; Linli Huang; Junyu Wu; Ge Song; Hongwei Ni; Haiming Ying; Hao Yu; Yinbo Gan (Plant Molecular Biology, 2018)